Analysis of Primary Metabolite Compound Content in Tempe Durian Seeds (Durio zibethinus) - Siti Nuryanti; Sitti Rahmawati; Safna Nurfadila; Anang Wahid M. Diah; Sri Mulyani Sabang; Dewi Satria Ahmar (Postgraduate, University of Mataram, 2024)
Durian seed tempe is tempe made from durian seed waste through a fermentation process by the same microorganisms used to make soybean tempe, namely Rhizopus sp. This research aims to determine the content of primary metabolite compounds in durian seed tempe. The process of determining the fat content in durian seed tempe uses the soxhletation method with n-hexane solvent. The protein content is determined using the Kjedhal method, which uses 3 processes, namely digestion, distillation, and titration. Meanwhile, carbohydrate levels are determined using the anthrone method. Based on the results obtained in this research, namely: the results of the analysis of the fat content contained in durian seed tempe were 0.006 grams. The protein content in durian seed tempe is 0.216, and the carbohydrate content in durian seed tempe is 2.421 grams